2020
DOI: 10.3389/fpls.2020.535005
|View full text |Cite
|
Sign up to set email alerts
|

Bioaugmentation of Entomopathogenic Fungi for Sustainable Agriotes Larvae (Wireworms) Management in Maize

Abstract: Soil microorganisms influence biotic and abiotic stress tolerance of crops. Most interactions between plant symbiotic and non-symbiotic soil microorganisms and plants occur in the rhizosphere and are sustained through plant exudation/rhizodeposition. Bioaugmentation, i.e., the introduction or amplification of certain plant beneficial microbes (e.g., entomopathogenic fungi) into the rhizosphere, could contribute to controlling insect crop pests and replacing chemical, environmentally unfriendly insecticides. Wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…The effects of coating maize seeds with Metarhizium are often beneficial. Razinger et al [44] reported a significant increase in fresh weight of maize by coating seeds with M. robertsii, but no effect on plant length, whereas colonized maize plants of Ahmad et al [1] were greater in length and shoot biomass. Kabaluk and Ericsson [56] treated maize seeds with Metarhizium anisopliae (Metschn.)…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The effects of coating maize seeds with Metarhizium are often beneficial. Razinger et al [44] reported a significant increase in fresh weight of maize by coating seeds with M. robertsii, but no effect on plant length, whereas colonized maize plants of Ahmad et al [1] were greater in length and shoot biomass. Kabaluk and Ericsson [56] treated maize seeds with Metarhizium anisopliae (Metschn.)…”
Section: Discussionmentioning
confidence: 97%
“…Metarhizium robertsii isolates (2698, 2700 and 2154) also significantly prolonged the emergence time. Razinger et al [44] and Kuzhuppillymyal-Prabhakarankutty et al [45] also reported a lower germination rate of maize seed; this could be a consequence of the method by which the conidia were applied to the seeds, namely by using carboxymethyl cellulose or methylcellulose. In our case, the maize seeds were soaked in a suspension of fungal conidia using only 0.1% Tween 80 to overcome the difficulties with the hydrophobic properties of the conidia of the fungal species under study and to allow adequate adhesion of the conidia to the maize kernels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The multifunctional use of bio-inocula [101][102][103][104] could be exploited to support the development, marketing, and application of microbial-based products. However, the current legal framework in the European Union, as well as in other countries, on the production and marketing of microbial-based products poses serious challenges to exploit the multifunctionality of beneficial microbes.…”
Section: Fermentation and Formulation Of Bioinoculantsmentioning
confidence: 99%
“…For this reason, fungal adaptation, especially in agroecosystems, has been viewed as a crucial attribute that needs to be evaluated for any entomopathogenic fungal (EPF) candidates before their field application. Some Metarhizium species, for example, M. anisopliae , M. brunneum and M. robertsii, demonstrate a strong association in the soil environment in terms of rhizosphere colonization [ 19 , 20 ] and endophytic establishment in plant roots, for example, in cassava [ 21 ] and in tomato [ 22 ]. Fungal–plant interactions, such as endophytism or rhizosphere competence, can confer crop protection against root herbivores [ 20 ] and even result in the suppression of root herbivores by altering the gene expression of the host plant [ 23 ].…”
Section: Introductionmentioning
confidence: 99%